2013
DOI: 10.1371/journal.pone.0078554
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of High Fat Diet on Indices of Metabolic Syndrome in 3xTg-AD Mice: Implications for Alzheimer's Disease

Abstract: Multiple factors of metabolic syndrome have been implicated in the pathogenesis of Alzheimer's disease (AD), including abdominal obesity, insulin resistance, endocrine dysfunction and dyslipidemia. High fat diet, a common experimental model of obesity and metabolic syndrome, has been shown to accelerate cognitive decline and AD-related neuropathology in animal models. However, sex interacts with the metabolic outcomes of high fat diet and, therefore, may alter neuropathological consequences of dietary manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 51 publications
8
74
3
Order By: Relevance
“…Here we observed that HFD significantly exacerbated Aβ burden and behavioral impairment when introduced in early life, prior to significant preexisting pathology. This finding is consistent with our previous observation that four-month exposure to HFD introduced at age 3 mo significantly increased Aβ load and worsened performance in the spontaneous alternation task in male and female 3xTg-AD mice [38]. Similar findings of worsened AD-related pathology by early exposure to high-fat and/or high sugar diets have been reported in other AD transgenic strains, including Tg2576 [54], APP Swe/Ind [55], and APP/PS1 [56].…”
Section: Discussionsupporting
confidence: 93%
“…Here we observed that HFD significantly exacerbated Aβ burden and behavioral impairment when introduced in early life, prior to significant preexisting pathology. This finding is consistent with our previous observation that four-month exposure to HFD introduced at age 3 mo significantly increased Aβ load and worsened performance in the spontaneous alternation task in male and female 3xTg-AD mice [38]. Similar findings of worsened AD-related pathology by early exposure to high-fat and/or high sugar diets have been reported in other AD transgenic strains, including Tg2576 [54], APP Swe/Ind [55], and APP/PS1 [56].…”
Section: Discussionsupporting
confidence: 93%
“…This relationship may be especially important for women, as women are both more at risk for AD (Li and Singh, 2014), and experience an increase in central adiposity at menopause (Meyer et al, 2011; Sugiyama and Agellon, 2012). While there exists some evidence of sex differences in obesity-associated AD risk (Barron et al, 2013; Hwang et al, 2010; Wolf et al, 2012), results are inconclusive and more work is needed to determine the nature of this relationship. Two factors that may be mechanistically important in the relationship between obesity and AD are apoE4 and inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…A commonly used approach is the use of high fat diet (HFD) in rodents, which yields diet-induced obesity (DIO). Using this model, our lab and others have shown that DIO in transgenic mouse models of AD increases levels of Aβ (Barron et al, 2013; L. Ho et al, 2004; Julien et al, 2010; Kohjima et al, 2010), a key protein in the initiation and progression of AD (Selkoe, 2011).…”
Section: Obesity/metabolic Syndrome As Risk Factors For Admentioning
confidence: 99%
See 2 more Smart Citations